Nafkah Suami dan Istri Bekerja Persfektif Imam Mazhab - Willy Zulfan; Heri Firmansyah (JOURNAL SAINS STUDENT RESEARCH, 2026)
Marriage is a noble Islamic institution; this nobility stems from the fact that in marriage, a husband does not merely make a promise to his wife and her guardian, and vice versa, but in essence, they are making a promise to their Lord (mitsaqan ghalizan). It is this strong and noble covenant that compels a husband to fulfill his obligations as a husband toward his wife’s rights, so that, by extension, the husband is also entitled to his rights regarding what is required of his wife. In the Qur’an, Allah has established the rights and obligations of husbands and wives in marriage, one of which pertains to the financial support (nafkah) that a husband is obligated to provide for his wife. In essence, financial support is one of the obligations a husband must fulfill toward his wife; likewise, the wife is obligated to obey and be submissive to her husband because she has received her right from him in the form of financial support. However, issues and debates arise when the wife works to earn an income and sometimes even contributes to providing for the family’s financial needs. Therefore, in this article, the author aims to explain the rights and obligations of husbands and wives regarding spousal support for working spouses from the perspective of the four schools of Islamic jurisprudence. The purpose of this article is to ensure that every Muslim who intends to marry or is already married understands the rights and obligations Allah has established for them within the household, so that their marriage may be one that pleases God, bringing peace and mutual love to the relationship. The method used by the author in writing this article is the descriptive qualitative method, which involves explaining and elaborating in depth and objectively on the rights and obligations of husbands and wives regarding spousal support for working spouses according to the four schools of Islamic jurisprudence. The author concludes, based on the opinions of the imams of these schools, that spousal support is an absolute obligation of the husband toward his wife.